Morphology and Petrogenesis of Pillow Lavas from the Ganj Ophiolitic Complex, Southeastern Kerman, Iran - A.R. Shaker Ardakani (Journal of Sciences, Islamic Republic of Iran)
The Upper Cretaceous Ganj complex, a part of the Jazmurian ophiolitic belt, is located on the western boundary of Jazmurian depression and separated from Kahnuj ophiolitic complex by north-south trending Jiroft fault. The complex consists of lava flows, pillow lavas, acidic plutonic and sedimentary rocks which are intruded by northwest-southeast trending dykes. It does not resemble a classical ophiolitic sequence due to lacking of intrusive crustal and mantle sections. The basaltic pillow lavas occur as flattened-tubular shape normal and mega sized bodies with bread crust crack surfaces. They show three textural zones from surface to interior: glassy, glassy and crystalline, and holycrystalline. Each zone characterized by different textures and varying assemblages of plagioclase ± olivine ± pyroxene and opaque. The glassy surface of the pillows frequently consists of one or rarely multiple rinds: sideromelane, dark tachylyte; and tachylyte with elongated vesicles. On Nb/Y versus Zr/TiO2 and SiO2 versus Nb/Y diagrams the pillow lavas plot in the field of basalt and sub-alkaline respectively. The relatively low immobile trace elements ratios are another sign of their tholeiitic nature. The absence of Eu anomaly on chondrite-normalized REE patterns suggests insignificances of plagioclase fractionation, or magma was relatively oxidized. They are similar to transitional basalts that lie between enriched MORB and OIB and some BABB. However enrichment in incompatible elements, depletion in Nb and low La/Nb ratios (0.94-1.81) are signature of BABB. They were formed by 15-30% partial melting of plagioclase lherzolite where fractionation was controlled by removal of olivine, spinel and clinopyroxene.